Neuroanatomical heterogeneity and homogeneity in individuals at clinical high risk for psychosis - Baldwin, Helen; Kaess, Michael; Resch, Franz (Translational Psychiatry, 2022)
Individuals at Clinical High Risk for Psychosis (CHR-P) demonstrate heterogeneity in clinical profiles and outcome features. However, the extent of neuroanatomical heterogeneity in the CHR-P state is largely undetermined. We aimed to quantify the neuroanatomical heterogeneity in structural magnetic resonance imaging measures of cortical surface area (SA), cortical thickness (CT), subcortical volume (SV), and intracranial volume (ICV) in CHR-P individuals compared with healthy controls (HC), and in relation to subsequent transition to a first episode of psychosis. The ENIGMA CHR-P consortium applied a harmonised analysis to neuroimaging data across 29 international sites, including 1579 CHR-P individuals and 1243 HC, offering the largest pooled CHR-P neuroimaging dataset to date. Regional heterogeneity was indexed with the Variability Ratio (VR) and Coefficient of Variation (CV) ratio applied at the group level. Personalised estimates of heterogeneity of SA, CT and SV brain profiles were indexed with the novel Person-Based Similarity Index (PBSI), with two complementary applications. First, to assess the extent of within-diagnosis similarity or divergence of neuroanatomical profiles between individuals. Second, using a normative modelling approach, to assess the ‘normativeness’ of neuroanatomical profiles in individuals at CHR-P. CHR-P individuals demonstrated no greater regional heterogeneity after applying FDR corrections. However, PBSI scores indicated significantly greater neuroanatomical divergence in global SA, CT and SV profiles in CHR-P individuals compared with HC. Normative PBSI analysis identified 11 CHR-P individuals (0.70%) with marked deviation (>1.5 SD) in SA, 118 (7.47%) in CT and 161 (10.20%) in SV. Psychosis transition was not significantly associated with any measure of heterogeneity. Overall, our examination of neuroanatomical heterogeneity within the CHR-P state indicated greater divergence in neuroanatomical profiles at an individual level, irrespective of psychosis conversion. Further large-scale investigations are required of those who demonstrate marked deviation.
Autor:innen: Helen Baldwin, Joaquim Radua, Mathilde Antoniades, Shalaila S. Haas, Sophia Frangou, Ingrid Agartz, Paul Allen, Ole A. Andreassen, Kimberley Atkinson, Peter Bachman, Inmaculada Baeza, Cali F. Bartholomeusz, Michael W.L. Chee, Tiziano Colibazzi, Rebecca E. Cooper, Cheryl M. Corcoran, Vanessa L. Cropley, Bjørn H. Ebdrup, Adriana Fortea, Louise Birkedal Glenthøj, Holly K. Hamilton, Kristen M. Haut, Rebecca A. Hayes, Ying He, Karsten Heekeren, Michael Kaess, Kiyoto Kasai, Naoyuki Katagiri, Minah Kim, Jochen Kindler, Mallory J. Klaunig, Shinsuke Koike, Alex Koppel, Tina D. Kristensen, Yoo Bin Kwak, Jun Soo Kwon, Stephen M. Lawrie, Irina Lebedeva, Jimmy Lee, Ashleigh Lin, Rachel L. Loewy, Daniel H. Mathalon, Chantal Michel, Romina Mizrahi, Paul Møller, Barnaby Nelson, Takahiro Nemoto, Dorte Nordholm, Maria A. Omelchenko, Christos Pantelis, Jayachandra M. Raghava, Jan I. Røssberg, Wulf Rössler, Dean F. Salisbury, Daiki Sasabayashi, Ulrich Schall, Lukasz Smigielski, Gisela Sugranyes, Michio Suzuki, Tsutomu Takahashi, Christian K. Tamnes, Jinsong Tang, Anastasia Theodoridou, Sophia I. Thomopoulos, Alexander S. Tomyshev, Peter J. Uhlhaas, Tor G. Værnes, Therese A.M.J. van Amelsvoort, Theo G.M. Van Erp, James A. Waltz, Lars T. Westlye, Stephen J. Wood, Juan H. Zhou, Philip McGuire, Paul M. Thompson, Maria Jalbrzikowski, Dennis Hernaus, Paolo Fusar-Poli and the ENIGMA Clinical High Risk for Psychosis Working Group, The Enigmar clinical high risk for psychosis working group: Camilo de la Fuente-Sandoval, Sabrina Catalano, Daniela Hubl, Jason Schiffman, Enea D. Venegoni, Christine I. Hooker, Paul E. Rasser, Wenche ten Velden Hegelstad, Franz Resch, Imke L.J. Lemmers-Jansen, G. Paul Amminger, Xiaogang Chen, Kang Ik K. Cho, Birte Yding Glenthøj, Lieuwe de Haan, Matthew A. Harris, Wu Jeong Hwang, Pablo León-Ortiz, Xiaoqian Ma, Patrick McGorry, Ricardo Mora-Durán, Masafumi Mizuno, Merete Nordentoft,Lijun Ouyan, Jose C. Pariente, Francisco Reyes-Madrigal, Mikkel E. Sørensen, Dennis Velakoulis, Sophia Vinogradov, Christina Wenneberg, Hidenori Yamasue, Liu Yuan and Alison R. Yung
Gesehen am 07.09.2022